Transcriptome analysis of placentae reveals HELLP syndrome exhibits a greater extent of placental metabolic dysfunction than preeclampsia - Lili Gong; Huanqiang Zhao; Yutong Cui; Xiaotian Li (Hypertension in Pregnancy, 2021)
Objective: The association between HELLP syndrome and preeclampsia has been investigated with conflicting conclusions. This study is to investigate the pathogenesis underlying these two diseases by analyzing placental transcriptome. Methods: The gene expression profile downloaded from Gene Expression Omnibus database was analyzed by R language. Results: A total of 573 differentially expressed genes in HELLP syndrome and 358 in preeclampsia were identified, among which 295 were unique to HELLP syndrome. Some metabolism-associated pathways were uniquely enriched in HELLP syndrome. Conclusions: HELLP syndrome exhibits a greater extent of placental metabolic dysfunction than preeclampsia, although these two diseases might share partial pathogenesis